Farm to fork: Cairo’s food supply and distribution during the Mamluk sultanate (1250-1517) - Quickel, Anthony Teke (AUC Knowledge Fountain, 2015)
The wealth of Cairo’s markets throughout the Mamlūk period is well attested in the sources. From roving peddlers to stationary markets, the city’s food supply was a testament to Egypt’s agricultural bounty. This study attempts to understand the food economy that provisioned these food markets. In doing so, Egypt’s agricultural production, its transportation network, distribution system, and Cairo’s markets are discussed with a focus towards understanding both the nature of the many aspects of the Mamūk food economy as well as the changes occurring within it. In providing an overall description of the mechanisms by which the Mamlūk food economy functioned, this thesis argues that the structure of the system was an ongoing dialectic between the labor and efforts of the peasants, the activities of the food merchants and sellers, and the contrivances of those with power, especially the Mamlūk regime itself. The complexities of this system were not only influenced by the activities of these three groups but were also driven by environmental and geographic factors as well. When all of these factors worked in concert, an intricate, multi-layered system produced the abundance and wealth of Cairo’s markets that were evident for all to see. However, the effects of the plague, starting in the fourteenth century CE, combined with the labor-intensive nature of the Egyptian agricultural and transportation systems disrupted this multiplex system. The agricultural sector being key to the overall Mamlūk economy, this breakdown created the conditions from which the agricultural system and, correspondingly, the economy failed to recover.